DFT insights into the mechanism of O2 activation catalyzed by a structural and functional model of cysteine dioxygenase with tris(2-pyridyl)methane-based ligand architecture - Britto, Neethinathan Johnee; Jaccob, Madhavan; Comba, Peter; Anandababu, Karunanithi; Mayilmurugan, Ramasamy (Journal of inorganic biochemistry, 2023)
Cysteine dioxygenation is an important step in the metabolism of toxic L-cysteine (Cys) in the human body, carried out by cysteine dioxygenase enzyme (CDO). The disruption of this process is found to elicit neurological health issues. This work reports a computational investigation of mechanistic aspects of this reaction, using a recently reported tris(2-pyridyl)methane-based biomimetic model complex of CDO. The computed results indicate that, the initial SO2 bond formation process is the slowest step in the S-dioxygenation process, possessing an activation barrier of 12.7 kcal/mol. The remaining steps were found to be downhill requiring very small activation energies. The transition states were found to undergo spin crossover between triplet and quintet states, while the singlet surface remained unstable throughout the entire reaction. In essence, the mechanistic scheme and multistate reactivity pattern together with the relatively small computed rate-limiting activation barrier as well as the exothermic formation energy demonstrate that the model complex is an efficient biomimetic CDO model. In addition, the study also substantiates the involvement of Fe(IV)oxido intermediates in the mechanism of S-dioxygenation by the chosen model complex. The insights derived from the O2 activation process might pave way for development of more accurate CDO model catalysts that might be capable of even more efficiently mimicking the geometric, spectroscopic and functional features of the CDO enzyme.